THE EFFECTIVENESS OF DISTANCE LEARNING (PJJ) ON UNDERSTANDING THE CONCEPT OF STUDENTS ON SCIENCE SUBJECT IN SMPN KECAMATAN LAREH SAGO HALABAN - Yosi Hanifah; Tuti Lestari (Department of Science Education, 2021)
Due to the current Covid-19 Pandemic, learning in schools is being claimed to be less effective, as well as learning science in formal education. This is because face-to-face learning cannot be implemented between teachers and students at school. Teachers and students can only carry out learning online by Internet network. This study aims to determine the implementation, strengths and weaknesses that felt by teachers and students in online science learning at SMPN Lareh Sago Halaban. This research was conducted using a qualitative descriptive method. Sources of the data used are primary and secondary data sources. Data analysis techniques used are reduction, display, and conclusion / verification.Based on research that has been conducted through a questionnaire, that during distance learning (PJJ) there is still a lack of understanding of the concept of students towards science learning material and it is still not 100% well implemented.